Maximization of flower yield in safflower (Carthamus tinctorius L.): SAFFLOWER YIELD MAXIMIZATION - VRIJENDRA SINGH; N M KOLEKAR; N NIMBKAR (Journal of Oilseeds Research, 2013)
A study was carried out on a non-spiny hybrid safflower (Carthamus tinctorius L.) NARI-NH-1 for maximization of flower yield by altering the agronomic practices viz., dates of sowing, fertilizer levels and plant spacings. The study showed that the differences due to sowing dates, fertilizer levels and plant spacings were significant for flower and seed yield in safflower. Delayed sowing beyond first fortnight of October resulted in a decrease in both flower and seed yield. Significantly highest flower yield (199 kg/ha) and seed yield (2014 kg/ha) were recorded with an application of 150% recommended dose (RD) of fertilizers, with flower yield being 26.85% higher and seed yield 28.89% higher than the control. However, if the net returns are considered, there is no advantage in applying more than 100% RD of fertilizer to the crop. The spacing of 45 cm x 10 cm gave significantly higher flower and seed yield over the recommended spacing of 45 cm x 20 cm. The interaction effects between dates of sowing, spacings and fertilizer levels suggested that sowing of safflower in the first week of October either with a spacing of 45 cm x 10 cm and an application of 100% or 150% RD of fertilizer or with a spacing of 45 cm x 20 cm with an application of 150% RD of fertilizer can be recommended for obtaining maximum flower and seed yield in safflower.